1999
DOI: 10.1177/0893318999131002
|View full text |Cite
|
Sign up to set email alerts
|

Disseminating Information and Soliciting Input during Planned Organizational Change

Abstract: This study examined implementers’ uses of channels to disseminate information to and solicit input from staff members during planned change. How communication was differently directed to paid and volunteer staff and the degree to which channel use is predictive of implementers’assessments of success of change efforts was also assessed. Implementers of 89 planned change efforts across a wide variety of geographic and business sectors served as respondents for the study. Potential applications of findings for or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 33 publications
3
103
0
8
Order By: Relevance
“…Lewis (1999), Armenakis y Harris (2002) y House y Stank (2001) consideran que la aceptación del cambio por parte de los miembros de la organización depende de la forma como los directivos compartan la información. Por su parte, Kleinbaum, Stuart y Tushman (2008) refieren que la comunicación interpersonal es categorizada como sincrónica vs. sincrónica.…”
Section: Comunicación Organizacionalunclassified
“…Lewis (1999), Armenakis y Harris (2002) y House y Stank (2001) consideran que la aceptación del cambio por parte de los miembros de la organización depende de la forma como los directivos compartan la información. Por su parte, Kleinbaum, Stuart y Tushman (2008) refieren que la comunicación interpersonal es categorizada como sincrónica vs. sincrónica.…”
Section: Comunicación Organizacionalunclassified
“…Other than general information meetings, small informal discussions are the most frequently used channels for disseminating information, whereas written information is the least frequently used channel of communication (Lewis, 2011). In terms of formal and informal communication, Lewis (1999) found that informal channels are utilized more for disseminating information and requesting input from organizational members. Finally, Timmerman (2003) stated that source, organization, media, message, task, receiver, and strategic factors are likely to influence the selection of communication channels that agents employ to disseminate information.…”
Section: Wwwerciyes-akademiacommentioning
confidence: 99%
“…Although communication channels can be used for both disseminating information and asking for input, among other functions, Lewis (1999) found that change agents focus more on disseminating information than on soliciting input and invitations for participation. Based on these agents' perceptions, the selection of channels for disseminating information -especially use of general information meetings-is found to be related to successful change outcomes.…”
Section: Wwwerciyes-akademiacommentioning
confidence: 99%
See 1 more Smart Citation
“…As disseminators, the managers in a TQC organization will be responsible for relaying process efficiency, improvement, and customer satisfaction information to employees, as prescribed by a monarchical information structure, following a "top-down cascade model" (Cole, 1999, p. 199). This disseminator role is especially valued by employees in uncertain and risky environments, as mediated or top-level messages are too remote from users' actual activities to be highly credible, practical, or influential (Lewis, 1999). As spokespeople for a TQC organization, managers are an important carrier of the quality message to the organization's customers and environment, emphasizing product quality, process efficiency, and customer satisfaction.…”
Section: Managerial Informational Roles and Tqmmentioning
confidence: 99%